2016
DOI: 10.1038/ncomms12228
|View full text |Cite
|
Sign up to set email alerts
|

The feeder system of the Toba supervolcano from the slab to the shallow reservoir

Abstract: The Toba Caldera has been the site of several large explosive eruptions in the recent geological past, including the world's largest Pleistocene eruption 74,000 years ago. The major cause of this particular behaviour may be the subduction of the fluid-rich Investigator Fracture Zone directly beneath the continental crust of Sumatra and possible tear of the slab. Here we show a new seismic tomography model, which clearly reveals a complex multilevel plumbing system beneath Toba. Large amounts of volatiles origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(104 citation statements)
references
References 36 publications
(68 reference statements)
8
91
2
Order By: Relevance
“…In this case, it becomes clear that this anomaly might indicate the area of ascended magmas along a weakened fracture zone associated with a regional tectonic fault. Similar association of the volcano locations with tectonic faults is a rather common feature observed, for example, in the area of the Toba supervolcano (Koulakov et al, ) and Tolbachik in Kamchatka (Koulakov et al, ).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In this case, it becomes clear that this anomaly might indicate the area of ascended magmas along a weakened fracture zone associated with a regional tectonic fault. Similar association of the volcano locations with tectonic faults is a rather common feature observed, for example, in the area of the Toba supervolcano (Koulakov et al, ) and Tolbachik in Kamchatka (Koulakov et al, ).…”
Section: Discussionsupporting
confidence: 65%
“…Saint Helen has provided evidence of magmatic sources located below a thick layer of sediments (Bedrosian et al, ; De Siena et al, ), which is similar to our case. In another case of the Lunayyir basaltic field in Saudi Arabia, the attenuation tomography by Sychev et al () has revealed the traces of degassing in the upper crust, which were not detectable in the seismic velocity model (Koulakov et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on seismic attenuation in southeast Japan (Figure b), Saita et al () inferred two high‐fluid‐content zones separated by a low‐fluid‐content zone above the subducting slab. Similar structures are also found in the Sunda/Sumatra subduction zone underneath the Toba volcano (Koulakov et al, ) and in the central Andean subduction zone (Schurr et al, ). These geophysical images clearly indicate a diversion of fluid flow from vertically upward direction in these subduction zones.…”
Section: Introductionsupporting
confidence: 69%
“…The largest and most representative volcanic complex is Toba Caldera, located along a major bend in the subducting plate below, probably characterized by a tear reactivating a pre-existing fracture zone (Figure 1; Fauzi et al, 1996;Pesicek et al, 2008;Hall and Spakman, 2015;Koulakov et al, 2016). Toba is the site of Earth's largest Quaternary eruption, ejecting ∼3000 km 3 of magma, after at least 150,000 years of storage and evolution (Vazquez and Reid, 2004;De Silva et al, 2015).…”
Section: Tectonic Setting Of Sumatramentioning
confidence: 99%